A rare case of late onset reticulate acropigmentation of Kitamura without involvement of the palms and soles - Melly, Conny; Sularsito, Sri Adi; Sirait, Sondang Panjaitan; Rihatmadja, Rahadi; Widyasari, Indah; Onmaya, Vini (UI Scholars Hub, 2015)
Background: Reticulate acropigmentations of Kitamura (RAPK) is an autosomal dominant inherited disorder characterized by pigmented, angulated, irregular freckle-like lesion with atrophy on the surface, arranged in a reticulate pattern on the dorsa of the hands and feet. It was first described by Kitamura and Akamatsu in Japan in 1943. The usual age of onset is the first and second decades of life. Palms and soles reveal pits and breaks in the epidermal ridge pattern. The histopathological examination show epidermal atrophy, digitate and filiform elongated rete ridges with clumps of heavy melanin pigmentation at their tips. Case: A 59-year-old male presented with asymptomatic and progressive brownish-black discoloration in a reticulate pattern on the dorsal aspect of his hands and feet. The lesions initially appeared when the patient was 45 years old. It was not preceded by any erythema or inflammation. There was no similar case in the family. Laboratory findings were within normal limits. Discussion: Skin biopsy taken from the dorsal of the hand and foot revealed hyperkeratosis, thinning of epithelium, filiform elongation of the rete ridges, increased melanocyte numbers in the basal layer, and lymphocyte infiltration in the dermis. Based on the clinical and histological findings he was diagnosed as RAPK. From some reports, sporadic cases without the involvement of other family members may occur, like our patient. Palms and soles involvement in RAPK is still debated, some considered it as a characteristic sign of this disorder while others refuted it.